2017
DOI: 10.1111/vco.12357
|View full text |Cite
|
Sign up to set email alerts
|

Gain‐of‐function mutation in PTPN11 in histiocytic sarcomas of Bernese Mountain Dogs

Abstract: Histiocytic sarcoma (HS) is an aggressive malignant neoplasm of dendritic cell origin that is common in certain breeds of dogs. High prevalence of fatal, disseminated HS has been described in Bernese Mountain Dogs (BMDs). Support for genetic predisposition to develop HS has been presented in several studies, but to date, causative genetic events have not been reported. In addition, no driver mutations have been identified in tumours. Recently, E76K gain-of-function mutation in SHP2 encoded by the PTPN11 gene h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 37 publications
6
30
1
Order By: Relevance
“…As recently reported by our group, a gain-of-function mutation in PTPN11 was found to be associated with HS in BMDs (37). Activating mutations in the PTPN11 gene have also been reported in human HS cases (15,18,60,61).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As recently reported by our group, a gain-of-function mutation in PTPN11 was found to be associated with HS in BMDs (37). Activating mutations in the PTPN11 gene have also been reported in human HS cases (15,18,60,61).…”
Section: Discussionsupporting
confidence: 77%
“…As in humans, the MAPK pathway seems to contribute to HS in dogs, as exemplified through a gain-of-function mutation PTPN11 E76K , a gene that encodes SHP2, required for MAPK. This mutation was recently reported in canine HS by our group and found to be prevalent in BMDs compared with other breeds (37% vs. 9%) (37).…”
Section: Introductionsupporting
confidence: 65%
“…It has been shown that dogs with lymphoid neoplasia and mammary carcinoma had a higher amount of cfDNA in plasma than controls 19,20 , although this increase is not specific to cancer. Over the last 10 years, recurrent somatic alterations have been described in several canine cancers such as multicentric lymphoma 21,22 , histiocytic sarcoma (HS) [23][24][25][26][27] and oral malignant melanoma (OMM) [28][29][30][31][32] . Detection of such cancer-specific recurrent somatic alterations in ctDNA may allow to develop new minimally invasive biomarkers for diagnosis, prognosis and to assess treatment-response in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentation, histopathology and issue of this canine cancer are similar to those observed in humans 22,23 . These breed predispositions allowed the collection of numerous samples to successfully identify somatic variants of the MAPK pathway 24,25 and we recently showed that the same mutations of PTPN11, the most frequently altered gene of the MAPK pathway, are found in human and canine HS 25 . But most importantly, these breed predispositions to specific clinical presentations allow to unravel the genetic bases of HS.…”
Section: Introductionmentioning
confidence: 99%